A visual uprising: Framing the online activism of Bahrain's Shiʿi opposition. (September 2019) - Moore-Gilbert, Kylie
Drawing on content analysis and framing theory, this article examines the use of images in the social media activism of three Bahraini Shiʿi opposition groups throughout 2015: Al-Wefaq, a moderate political society in favour of constitutional monarchy; Haqq, an underground pro-republic political society; and the February 14 Coalition, a decentralized umbrella group of youth activists dedicated to overthrowing Bahrain's Al Khalifa monarchy. The differing ideologies, objectives and approaches to activism within Bahrain's Shiʿi opposition are investigated through an analysis of each group's framing of themes including religion, violence, nationalism and sectarianism. The first empirical study of social media image activism in post-Arab Spring Bahrain, this article reveals the increasing fragmentation of the Shiʿi opposition following the 2011 uprising, and makes a valuable contribution to the broader debate surrounding the changing nature of activism in an increasingly visual digital age.